PENTINGNYA AUDIT SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRESTASI KERJA - Trisnowati, Juni (Universitas Surakarta, 2012)
The existence of an audit of human resources can be seen as a support to help organizations meet the challenges it faces in terms of human resources perspective. Audit of human resources is important and absolutely must be done to determine whether the employees are working well and behave according to plan, Â very important for the company and for the employees concerned . Audit of human resources is a systematic examination and assessment, objective and documented the organizational functions that are affected by the management of human resources with the purpose of ensuring compliance with the principle of appropriateness, effectiveness and efficiency in the management of human resources to support the achievement of functional goals and objectives of the organization as a whole better for short-term , medium -term and long-term. The results of the audit of human resources will provide benefits to various parties including the benefits to the company, the organizations members or employees and for the community Keywords; human resource audits , performance